2008
DOI: 10.14411/fp.2008.025
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni glyceraldehyde 3-phosphate dehydrogenase is a lung-stage schistosomula surface membrane antigen

Abstract: Abstract. We have previously reported that Schistosoma mansoni larvae emerging from host lung at pH 7.5-7.8 and then fixed with diluted formaldehyde (HCHO) readily bind radiation-attenuated cercariae (RA) vaccine serum antibodies, as assessed by indirect membrane immunofluorescence (IF). Here we show that S. mansoni schistosomula emerging from lung pieces under 5% CO 2 (pH ≤7.3) readily bind RA vaccine serum antibodies, provided they have been incubated for 12 h at pH 7.5-7.8 in foetal calf serum-free RPMI med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 48 publications
3
15
1
Order By: Relevance
“…No adverse effects were noted in any treated mice, supporting the data showing that administration of 2,000 mg/kg ARA oil for a period of 4 weeks did not induce obvious signs of toxicity in Wistar rats (14). It is not clear whether in vivo ARA-mediated worm killing is predominantly due to production of ceramide (12,21) or to exposure of the parasite to the host effector immune cells, antibodies, and toxic molecules and radicals (8,29,30). Of note, S. haematobium, which displayed higher in vivo sensitivity to ARA than S. mansoni, was shown to be more sensitive than S. mansoni to in vitro ARA-mediated exposure of otherwise concealed surface membrane antigens (29).…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…No adverse effects were noted in any treated mice, supporting the data showing that administration of 2,000 mg/kg ARA oil for a period of 4 weeks did not induce obvious signs of toxicity in Wistar rats (14). It is not clear whether in vivo ARA-mediated worm killing is predominantly due to production of ceramide (12,21) or to exposure of the parasite to the host effector immune cells, antibodies, and toxic molecules and radicals (8,29,30). Of note, S. haematobium, which displayed higher in vivo sensitivity to ARA than S. mansoni, was shown to be more sensitive than S. mansoni to in vitro ARA-mediated exposure of otherwise concealed surface membrane antigens (29).…”
Section: Discussionsupporting
confidence: 56%
“…Second, while dead parasites did not show spasmodic body contractions as they did after PZQ treatment, electron microscopy studies revealed entire disruption of the outer lipid bilayers, the strength of which was correlated with the ARA concentration. Third, addition of the nSMase inhibitors CaCl 2 (15,23,29) and GW4869 (19,20,30) entirely protected the parasite from the lethal ARA actions, and nearly all worms remained viable beyond the 5-h exposure period.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations